Factors Affecting Internal Audit Reporting on Public Sector in Sri Lanka - Anojan, Vickneswaran (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2022)
The main purpose of this study is to identify significant factors affecting the effectiveness of internal audit reporting in public sector in the Northern Province, Sri Lanka. This study used the primary data collected from the heads of departments, divisions, and internal auditors in public sector in the Northern Province of Sri Lanka through the developed questionnaire. The regression analysis confirmed that the tested factors significantly affected the effectiveness of internal audit reporting, especially accountability and transparency, while internal auditor independence more significantly affected the effectiveness of internal audit reporting. All tested factors were significantly correlated with the effectiveness of internal audit reporting, except materiality. This study was based on the data collected from public sector in the Northern Province of Sri Lanka, therefore the findings of this study could be generalized to the other public sector organizations in the other provinces of Sri Lanka. According to the statistical results, it is suggested that the more the internal auditor independence of as well as internal auditor accountability and transparency, the more the effectiveness of internal audit reporting in public sector in the Northern Province of Sri Lanka. This is the first study evaluating significant factors affecting the effectiveness of internal audit reporting in public sector in Sri Lanka.